Diet reconstruction of the Sarmatians at Madaras. A preliminary survey - Smrčka, Vάclav; Jambor, Jaroslav; Marcsik, A. (Anthropological Review, 1994)
117 samples from the proximal femora were taken from 50 skeletons excavated from the Sarmatian cemetery at Madaras, situated on the southern part of the Hungarian Plain between the Danube and Tisza rivers. These skeletons date from the 3rd to the 5th century A.D. A trace element analysis was used in order to reconstruct their basic diet. The primary part of the Sarmatians' diet was vegetable as Sr, levels were high whereas the Zn levels were low. Low Pb concentrations in the. Sarmatians' bones, as compared to those of surrounding populations, testify to the low Pb of those surrounding populations, testify to the low Pb contamination in their diet.